PELATIHAN DAN PENDAMPINGAN PENGOLAHAN SAMPAH MENJADI PRODUK BERNILAI EKONOMI PADA BANK SAMPAH BERSIH BERSAMA KARANGANOM, SITIMULYO, PIYUNGAN, BANTUL - Budiyanto, Tri; Astuti, Reni Dwi; Purwani, Annie (Universitas Ahmad Dahlan, 2020)
Theâ€œBersih Bersamaâ€ Waste Bank located in Karanganom, Sitimulyo, Piyungan, Bantul, Yogyakarta Special Region was a waste bank that still exists to manage waste from the local community. The problems faced include that management ware still limited to receiving from customers, then collected and handed over to collectors. The customer was not always doing the sorting process, so the managers have to sort and even have to clean it first. In addition, the level of community awareness to manage waste is still lacking. The purpose of community service was to provide additional skills to members of the waste bank to convert used goods that were originally only sorted and sold, converted into products that have use value and sale value. Community service activities were carried out by organizing training and assistance in making coffee sachet bags using waste paper and coffee sachets (plastic) directly to the community. This training was carried out in 2 stages, namely on September 20 for stage 1 and October 10, 2020 for stage 2. The results of the implementation of community service were increased knowledge about the use of paper and plastic waste, the ability to make new products in the form of coffee sachet bags with attractive motifs that have value. added. A positive impact can be seen from the increased knowledge and understanding of waste bank members in the use of paper and plastic waste into useful and economic goods. In addition, the Karanganom Sitimulyo community can contribute to reducing plastic waste in their environment